Does age modulate the impact of import competition on job type? - Paz, Lourenco (Economics and Business Letters, 2022)
This study investigates the effects of the 2000–2012 increase in import competition in the Brazilian economy on the type of manufacturing jobs available to different age groups. These effects are assessed using a multinomial logit model and household survey data that cover formal, informal, and self-employed workers. The empirical estimates indicate that an increase in the Chinese or in the rest of the world import penetrations expand self-employment only among young workers. Larger Chinese imports reduce self-employment for middle-aged workers. In contrast, greater imports from elsewhere increase informality across all age groups, though the magnitude is decreasing in age. These estimates are robust to endogeneity concerns through the use of a control function approach.